Depression in Diabetes: A cross sectional survey among patients attending Diabetes Clinic in Kathmandu - Bhattarai, J.; Kunwar, A.; Shrestha, P.; Acharya, S.; Sah, R.P. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Depression, being a leading cause of disability, is a common illness affecting an estimated 350 million people affected worldwide and is a major contributor to the global burden of disease3. Depression is a significant comorbid condition prevalent in people with diabetes and adversely affects health outcomes. Methods: A cross sectional study was conducted on 434 patients in Metro Polyclinic situated in Kathmandu district of Nepal. Metro polyclinic was purposively selected as the sampling frame for this study as this polyclinic receives significant number of diabetes patients coming in from various regions of Nepal. Results: Among type -1 diabetes 55% had depression whereas 45% were normal. Among Type -2 diabetes 31% of them had depression whereas 69% had no depression. Among a total of 434 study sample, 425 were suffering from Type-2 diabetes while only nine of them were suffering from Type-1 diabetes. Of those who were suffering from Type-2 diabetes, 13 had severe depression, 27 had moderate depression, 85 had mild depression and 300 had normal range of depression. Conclusion: This study sheds the importance of looking for depression in Nepali diabetes patients. It has been shown that without identifying co-morbid depression and treating it, most of the patient will have poor prognosis.